Kuntowijoyo’s Islamic Scientific Methodology: Integration and Objectification towards Humanist Science - Andi Qadri Al-Aqsha; Agus Wahyu Triatmo (AN NUR: Jurnal Studi Islam, 2026)
The development of modern civilization demands that religion address complex issues, but text-centered understanding often creates a distance between sacred teachings and social reality. Responding to the stagnation and apologetic nature of the Islamization of knowledge movement, Kuntowijoyo offers a paradigm for Islamic scholarship. This article aims to examine the operationalization of the epistemological shift from text to context through methods of integration and objectification toward humanistic science. This qualitative research uses a library research approach with the primary data source from Kuntowijoyo’s literature, specifically Paradigma Islam: Interpretasi untuk Aksi. The collected data were analyzed using content analysis techniques and descriptive-analytical methods. The results of the study indicate that Islamic scholarship places the Qur’an as a construction of knowledge (mode of thought) to transform the people’s perspective from myth and ideology to empirical science. This transformation was achieved through integration, namely combining revelation and reason within a theoanthropocentric framework, and objectification, which translates the internal normative values of Islam into rational scientific formulations that are universally accepted by the public. This methodological synergy gave birth to Prophetic Social Science that is firmly based on the pillars of humanization, liberation, and transcendence. It is concluded that Kuntowijoyo’s methodology of integration and objectification has proven capable of transcending the limitations of previous movements and has succeeded in building a strong operational foundation for humanist Islamic science that actively solves the problems of modern humanity without losing its divine roots.